2013
DOI: 10.1080/09585192.2013.778313
|View full text |Cite
|
Sign up to set email alerts
|

Gender gap, training and financial performance: evidence from public accounting industry

Abstract: This study examines the effects of training on organization-level financial performance for male-owned and female-owned audit firms. We define audit firms whose auditors take professional training as non-violator firms and whose auditors do not take professional training as violator firms. Regression results indicate that financial performance of non-violator audit firms is better than that of violator firms. Maleowned audit firms are superior in financial performance to female-owned ones. Maleowned violator f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…The existing literature has focused heavily on the link between TMT or the boardroom and the firm's financial performance in western countries, and only a few empirical works have been undertaken to examine the relationship in Taiwan or other Asian countries (Julizaerma and Sori, 2012;Yang, Chen, and Yang, 2013;Low, Roberts, and Whiting, 2015). Also, few researchers have examined this issue at the partner level.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…The existing literature has focused heavily on the link between TMT or the boardroom and the firm's financial performance in western countries, and only a few empirical works have been undertaken to examine the relationship in Taiwan or other Asian countries (Julizaerma and Sori, 2012;Yang, Chen, and Yang, 2013;Low, Roberts, and Whiting, 2015). Also, few researchers have examined this issue at the partner level.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, professional training fills the gap left by academic education. As the third purpose of this study, we further examine the moderating effects of professional training on higher academic qualifications of auditors.Prior researches employ a linear relationship to examine the association between human capital and operating performance of audit firms [10][11][12]. When more auditors with a master's degree or above are hired, audit firms assume higher human capital cost, thus resulting in lower operating profits.…”
mentioning
confidence: 99%
“…Prior researches employ a linear relationship to examine the association between human capital and operating performance of audit firms [10][11][12]. When more auditors with a master's degree or above are hired, audit firms assume higher human capital cost, thus resulting in lower operating profits.…”
mentioning
confidence: 99%
“…These findings suggest that sex stereotypes may vary across cultures and that discrimination against women in the workplace is less severe in Northern European countries as compared to Taiwan, where Confucianism advocates the masculine social value that women should stay at home and be responsible for the household, while men are the breadwinners and leaders of the family (Chan et al, 2002;Yang et al, 2013). For example, Penner and Paret (2008) suggested that Asian kindergarten boys perform best on entering kindergartens, while Latino kindergarten girls perform better than Latino boys.…”
Section: Resultsmentioning
confidence: 93%
“…Relatedly, Yang, Chen, and Yang (2013) show that in Taiwan man-owned audit firms outperform woman-owned audit firms in financial performance, and even the formers without professional trainings on auditors have higher financial performance than the latters with professional trainings. The authors interpret these findings as suggesting "the Chinese cultural values in social roles against women".…”
Section: Introductionmentioning
confidence: 97%